After-Ripening Is Associated with Changes in the Sensitivity of Avena fatua L. Caryopses to Abscisic Acid, as Well as Changes in the Abscisic Acid and Bioactive Gibberellins Contents in Embryos - Jan Kępczyński; Agata Wójcik; Michał Dziurka (Plants, 2025)
The information on the involvement of hormones in the release of dormancy in grass caryopses is still insufficient. The main aim of the present study was to deepen our understanding of the mechanism dormancy release in Avena fatua L. caryopses by after-ripening in relation to abscisic acid (ABA) and gibberellins (GAs). The after-ripening of florets during dry storage resulted in dormancy removal in caryopses, allowing their germination at 20 to 30 °C. Sensitivity to ABA and paclobutrazol (PAC), a GAs biosynthesis inhibitor, decreased as the after-ripening period was extended. After-ripening increased the ABA content in the embryos of dry caryopses and decreased the total content of bioactive GAs, except for GA1, the content of which increased. Accordingly, the ABA/GAs ratio was increased, and the ABA/GA1 ratio was lowered due to after-ripening. After-ripening led to a decrease in the ABA content and increased the bioactive GAs contents, including GA1 and GA6, regarded as the most important for germination, in the embryos within 18 h of caryopses germination. The results obtained indicate that the embryos of dormant caryopses contained sufficient levels of bioactive GA1 and GA6 at early stages of germination, but their germination was prevented due to having too high an ABA concentration. It seems that the agents most important in dormancy removal through after-ripening include a reduction in the ABA content and sensitivity, as well as an increase in the bioactive GAs, particularly GA1 and GA6, in the embryos of germinating caryopses, which brings about a reduction in the ABA/GAs, ABA/GA1, and ABA/GA6 ratios, thus enabling germination.